Case report: Xeroderma pigmentosum Group A with erythropoietic protoporphyria in a young Chinese patient - Wu, Shu-hui; Xiao, Ting; Zhao, Dan; Zeng, Ying-hong; Zhu, Ming-fang (Frontiers in Endocrinology, 2024)
Xeroderma pigmentosum is a rare autosomal recessive genodermatoses characterized by a deficiency in nucleotide excision repair. Erythropoietic protoporphyria is a rare inherited metabolic disease caused by the perturbation of heme. Xeroderma pigmentosum-erythropoietic protoporphyria is exceedingly rare. Hereby, we firstly report a young Chinese patient of xeroderma pigmentosum Group A with erythropoietic protoporphyria carrying an XPA Met214AsnfsTer7 frameshift mutation and a homozygous splicing mutation, c.315–48T>C, in the proband’s intron3 of FECH.